1994
DOI: 10.1007/bf02349282
|View full text |Cite
|
Sign up to set email alerts
|

Use of immobilized histidine in assay for endotoxin in patients with liver disease

Abstract: The Limulus amebocyte lysate (LAL) test has the disadvantage of being influenced by various inhibitors and activators. We have developed a method for the LAL reaction that involves the specific adsorption and isolation of endotoxin using a membrane filter unit and immobilized histidine; in this present study we used the method to measure endotoxin in the plasma of patients with acute or chronic liver disease. The adsorbed endotoxins are separated from LAL-inhibitors or -activators by the membrane filter unit, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2000
2000
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…11,12 Last, but not least, the interpretation of endotoxin levels in patients with liver disease is particularly challenging, as they may be related to a reduced clearing efficiency of the hepatic reticuloendothelial system and/or an increased presence of liver-derived X-l,3-D-glucans, which can account for false-positive results. 13,14 In view of these concerns, there is an urgent need for an alternative method to assess endotoxin exposure of the liver in human NASH using peripheral blood. For this purpose, we here assessed the level of Immunoglobulin G (IgG) antibodies in the systemic circulation directed against the inner core of endotoxin, using the Endotoxin Core Antibodies assay (EndoCab).…”
mentioning
confidence: 99%
“…11,12 Last, but not least, the interpretation of endotoxin levels in patients with liver disease is particularly challenging, as they may be related to a reduced clearing efficiency of the hepatic reticuloendothelial system and/or an increased presence of liver-derived X-l,3-D-glucans, which can account for false-positive results. 13,14 In view of these concerns, there is an urgent need for an alternative method to assess endotoxin exposure of the liver in human NASH using peripheral blood. For this purpose, we here assessed the level of Immunoglobulin G (IgG) antibodies in the systemic circulation directed against the inner core of endotoxin, using the Endotoxin Core Antibodies assay (EndoCab).…”
mentioning
confidence: 99%
“…The liver plays an important role in innate immunity; its functions include reserving fixed‐tissue macrophages, including Kupffer cells, and regulating the synthesis of proteins responsible for pathogen recognition and opsonization [25]. Previous studies have reported that innate immunity impairment due to liver dysfunction after liver surgery was associated with both changes in innate immune response and postoperative infection [26–28]. Meanwhile, we demonstrated that RLHA division was an independent risk factor for postoperative transaminase elevation, suggesting the possible presence of innate immune impairment in patients with RLHA division.…”
Section: Discussionmentioning
confidence: 74%